Economic growth and public debt under a declining population. - Hansen, Arne (Tectum, 2013)
The economic effects of a rising population have been studied by many researchers, several countries will face a declining population in the near future or are even facing it already. How will this affect economic growth and public debt? The author analyzes the economic consequences of a declining population using both a model of the closed economy and a model of the small open economy, in order to account for the specific characteristics of open economies. For each model, he discusses the long-run effects and the transitional dynamics.
Keywords: Finanzwesen; Haushaltswesen; Staat; Verschuldung; Öffentliche Einnahmen; Öffentliche Ausgaben; Bevölkerungsentwicklung; Schrumpfung; Wirtschaftswachstum; Volkswirtschaft